PHYSICO-CHEMICAL PROPERTIES OF SOIL IN FOREST AND AGRO ECOSYSTEMS IN WARANGAL DISTRICT, TELANGANA STATE, INDIA (CAHIERS MAGELLANES-NS, 2024)
This study investigates the physico-chemical properties of soil in agricultural and forest ecosystems within Warangal District, Telangana, to understand how land use affects soil quality across different seasons. The objective was to compare soil pH, moisture, organic carbon, and electrical conductivity between these ecosystems during winter, summer, and monsoon. Soil samples were systematically collected from both ecosystems in each season and analyzed for the aforementioned parameters. The present study was conducted in the Rajanpalle village in Gudur mandal in Warangal district of Telangana state, India. The results reveal that forest soils generally exhibit higher pH, moisture content, and organic carbon levels compared to agricultural soils, reflecting the benefits of natural vegetation and organic matter accumulation. Specifically, forest soils maintain more stable moisture and organic carbon levels, particularly in winter, while agricultural soils show greater variability, especially in organic carbon content, which decreases in summer. Electrical conductivity remains within safe limits for both ecosystems, although agricultural soils have higher conductivity during the monsoon due to increased soluble salts from irrigation and rainfall. These findings underscore the significant impact of land use on soil properties and highlight the importance of implementing sustainable management practices to improve soil health and productivity in agricultural systems while preserving the advantages of forest ecosystems.